Plant diversity after sixteen years post coal mining in East Kalimantan, Indonesia - LIRIS LIS KOMARA; DEVI NANDITA CHOESIN; TATI SURYATI SYAMSUDIN (Society for Indonesian Biodiversity, 2016)
Komara LL, Choesin DN, Syamsudin TS. 2016. Plant diversity after sixteen years post coal mining in East Kalimantan,Indonesia. Biodiversitas 17: 531-538. Post coal mining areas need to be rehabilitated through reclamation and revegetation. The objective of this study was to evaluate plant diversity after 16 years of revegetation activities in a coal mining reclamation site in East Kalimantan. In an effort to restore plant diversity, the coal mining company began by planting fast growing species as pioneers, then planting local species after three years. This study compared a 20 hectare reclamation site with conditions in the pre-mining area, which covered 14,988 hectares. Vegetation sampling was conducted in 20 plots measuring 20x20 m2 along line transects, with 100 m distancebetween plots. A total of 104 plant species were found in the reclamation site, consisting of 76 tree species and 28 herbaceous species. Tree species consisted of 35 planted local species (e.g., Dryobalanops aromatica, Eusideroxylon zwageri, Macaranga gigantea), 25 planted non-local species, and 16 local species that grew spontaneously (e.g., Leucaena glauca, Lansium domesticum, Shorea laevis). In comparison, 133 species were found in the pre-mining site, consisting of 132 local tree species, one non-local tree species (Acacia mangium) and 52 herbaceous species. Tree species diversity index in the reclamation site after 16 years post mining (i.e., 3.54) was stilllower than in the pre-mining area (4.29); while the diversity indices for herbaceous plants were relatively similar (2.97 and 2.67 in the reclamation and pre-mining sites respectively). The slightly higher diversity of herbaceous plants in the reclamation site may be attributed to higher coverage per species in this site, despite lower species richness.